Sentiment Analysis of Twitter Netizens on Hashtag #Gitasav towards Childfree Opinion Using Social Network Analysis - Maslahul Adi, Nur Romdlon; Shafira, Adila Ardalia Shafira Rahmatika; Virgiananda, Ardhita Septi (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2023)
Childfree has become a hot topic of conversation, especially on Indonesian social media. Gita Savitri's controversial statement about her decision to be childfree program uploaded on her personal Instagram video reels attracted the attention of Indonesian netizens and eventually became trending on Twitter. According to Gita Savitri, childfree is the secret to staying young and having many children can make a woman look older. The pupose of this research is to determine the sentiment of netizens towards Gita Savitri's statement on the social media Twitter. This research uses the SNA or Social Network Analysis method using a web-based application, Netlytics.org. The result of this study is indicate that there is a positive sentiment in the statement childfree makes women look younger. Some netizens support this statement, but not many also disagree. There are 10 accounts whose tweets are most responded to, such as @hoshii071, @strategi_bisnis, @bemynotomymin, @fakhta, @thisisreparo, @footycinephile, @fikfinicky990, @yogisuprastrian, and @mufalbania. Therefore, in this article we will discuss netizen sentiment regarding Gita Savitri's statement regarding childfree making the face look youthful.